Actividad inhibitoria del extracto de hojas de Justicia spicigera Schltdl y hojas de Mangifera indica L. Sobre α – glucosidasa - Ipushima Hualinga, Alessander (2024)
Inhibiting the enzymes responsible for the catalytic process of carbohydrates is important to treat postprandial hyperglycemia. Our objective in this study was to determine the inhibitory activity of the leaf extracts of Justicia spicigera Schltdl. and leaves of Mangifera indica L. on α - glucosidase, where each organ of the plant species was collected for convenience, from these ethanolic extracts were prepared and tested at 100, 250, 500 and 1000 µg/mL. The results show that only the extracts of J. spicigera – leaves demonstrated to have a higher percentage of inhibition at the highest concentration evaluated; the IC50 obtained for the extracts of J. spicigera Schltdl. – leaves is considered active (IC50=986.14 µg) unlike the extract of M. indica L – leaves which requires a higher concentration than what was evaluated; allowing us to conclude that the extract of J. spicigera – leaves is active against the enzyme α-glucosidase.